A case of Rosai-Dorfman Disease - a rare case diagnosed on FNAC - Binaya Shrestha,; Soniya Shrestha,; Dipika Basnet,; Nikita Gautam, (Janaki Medical College Journal of Medical Science, 2024)
Background & Objectives: Sinus histiocytosis with massive lymphadenopathy (SHML) also known as Rosai-Dorfman Disease is a rare histiocytic proliferative disorder which can often be misdiagnosed as lymphoma clinically. On Fine Needle Aspiration Cytology (FNAC) very few cases of SHML have been diagnosed. The aim was focused on the cytological characteristics of the Rosai‑Dorfman disease and differential diagnoses. Presentation of Case: Here, we present a case of Rosai-Dorfman Disease in a 12 year old girl presented with a painless swelling over left side of neck. Discussion: Rosai‑Dorfman disease which is a rare histiocytic disorder involves mainly the lymph nodes and also extra nodal sites like head and neck. Most patients with RDD have spontaneous remission but few cases can be fatal. The differential cytological diagnosis includes reactive lymph node hyperplasia, infectious lymphadenitis, hemophagocytic syndrome, Langerhans cell histiocytosis and lymphoma. Conclusion: RDD is rare and require knowledge of its cytological characteristics for a rapid and correct diagnosis. FNAC is enough for the final diagnosis of the disease.